Pembuatan Profil Desa Tamboo Berbasis Web Desa Tamboo Kecamatan Bone Pantai Kabupaten Bone Bolango - Taufiq Ismail Yusuf; Ikhsan Hidayat; Sardi Salim; Ade Irawaty Tolago; Rahmat D.R. Dako; Amiruddin Y Dako; Sri Wahyuni Dali (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
In the previous service, initial observations that had been carried out with village officials, aimed at getting an initial picture of village conditions and observing the management and operational processes of village government, found that this village did not yet have a complete village profile document (as regulated in Minister of Home Affairs Regulation No. 12 of 2007 concerning Guidelines for Compilation and Utilization of Village and Sub-District Profile Data, does not yet have a village monograph, village map, village website and existing data are not integrated in a complete village profile document). The purpose of this service is to create a village profile in the form of a web/page so that village governance is more organized, transparent, and widely disseminated. The expected output targets of this activity are: Apparatus and the community in Tamboo Village have a village website page that can be managed alone. Village website consisting of: village profile data, population data, village resource and potential data and other activities that can be digitized for work effectiveness and efficiency.